2006
DOI: 10.1097/00006199-200609000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analytic Study of Predictors for Loneliness During Adolescence

Abstract: Theories of loneliness served as a framework for interpreting the findings of the meta-analysis. The most powerful predictors can be used in intervention studies aimed at reducing loneliness in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
98
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(120 citation statements)
references
References 15 publications
20
98
0
2
Order By: Relevance
“…People receiving more support reported less loneliness (Chen, Hicks, & While, 2014;Henninger, Eshbaugh, Osbeck, & Madigan, 2016;Zhao, Kong, & Wang, 2013). In a meta-analysis social support emerged as a significant predictor of loneliness with a medium effect size (Mahon et al, 2006). This is consistent with studies which demonstrated that perceived social support is a relevant construct in reducing loneliness (Adamczyk, 2016;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…People receiving more support reported less loneliness (Chen, Hicks, & While, 2014;Henninger, Eshbaugh, Osbeck, & Madigan, 2016;Zhao, Kong, & Wang, 2013). In a meta-analysis social support emerged as a significant predictor of loneliness with a medium effect size (Mahon et al, 2006). This is consistent with studies which demonstrated that perceived social support is a relevant construct in reducing loneliness (Adamczyk, 2016;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…In a meta-analytic study self-esteem emerged as one of the most powerful predictors of loneliness with a large effect size (Mahon et al, 2006). Individuals more likely to feel low selfesteem may blame themselves for having low social contact, and thus reinforce their loneliness (Perlman & Peplau, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies have found that loneliness is significantly correlated with depressive symptoms across time in children and adolescents (Hall-Lande, Eisenberg, Christenson, & NeumarkSztainer, 2007;Nangle, Erdley, Newman, Mason, & Carpenter, 2003;Qualter, Brown, Munn, & Rotenberg, 2010;Rotenberg et al, 2004;Vanhalst et al, 2012). Mahon et al (2006) reported that the correlation between loneliness and depressive symptoms in adolescents was in the range of a large effect size (r = 0.61 to 0.62).…”
Section: The Relationship Between Loneliness and Depressive Symptomsmentioning
confidence: 99%
“…In addition, three indicators of psychological adaptation were selected, that is, self-esteem, life satisfaction, and positive attitude toward the future. Reference correlations derived from research on the full-length version of the loneliness instrument (i.e., the UCLA-R) were taken from the appropriate sources (i.e., Russell et al, 1980, for the self-labelling index of loneliness; Mahon,Yarcheski, Yarcheski, Cannella, & Hanks, 2006, for depressive symptoms; Joiner & Rudd, 1996, for suicidal ideation; Mahon et al, 2006, for self-esteem;and Neto & Barros, 2000, for life satisfaction and general optimism, which was considered a proxy for positive attitude about the future).…”
Section: The Present Studymentioning
confidence: 99%